تصميم منصة دفع الكتروني للحجوزات في وكالة سياحة وسفر - أبا علي – غيوط أحمد بن سالم – مهيش فيصل (university of eloued جامعة الوادي, 2024)
يهدف مشروعنا لإنجاز موقع ويب يحجز عروض العمرة لدى وكالة اسفار وسياحة ليسهل من آلية الحجز والدفع إلكترونيا ويقضي على العناء والمشقة التي يتعرض لها الزبائن اثناء الحجز والدفع، وخلال هذا قمنا بدراسة أولية بدراسة أولية قمنا باستخلاص عيوب ونواقص الحجز والدفع عند الوكالات السياحية، التي بدورها مهدت لنا المتطلبات والخدمات التي يجب ان تتوفر في هذا الموقع ولعرض تلك الخدمات استخدمنا مخططات الUML ، وفي الأخير انجزنا الموقع باستخدام HTML و CSS و javaScript ... وربطه بقاعدة البيانات MySQL باستخدام اطار عمل Laravel عن طريق برمجته بلغة PHP. Our project aims to accomplish a web site that reserves Umrah offers at the travel and tourism agency to make it easier for the mechanism of reservation and payment electronically and eliminates the trouble and hardship that customers are exposed to during the reservation and payment, and during this we carried out a preliminary study in a preliminary study we extracted the defects and deficiencies of reservation and payment at tourism agencies, which in turn paved We have the requirements and services that must be available on this site and to display these services. We used UML charts, and in the end we have completed the site using HTML, CSS and JavaScript ... and linking it to MySQL database using the Laravel framework by programming it in PHP.
مدكرة ليسانس اعلام الي
Keywords: HTML; CSS; JavaScript; PHP; الحجز; الدفع الالكتروني; عمرة.; Reservation; Electronic Payment; Umrah